High/Other Looks. Different ‘Points of View’ in 20th Century Art (diségno, 2023)
In 1960 Jorge Luis Borges (1899-1986) published El hacedor, a collection of short stories and poems through which he narrates personal events and impressions, something unusual for the Argentine writer. [read more]